Perancangan Aplikasi Text To Speech Untuk Informasi Gempa Bumi - Supriyanto, Joko; Fadlil, Abdul; Sunardi, S (STIKOM Tunas Bangsa Pematangsiantar, 2022)
Indonesia is one of the countries with the potential of large earthquakes because it is passed by three active plates, namely Indo-Australian, Eurasian, and Pacific. Earthquake information is currently still in text form, so the blind have difficulty getting earthquake information. It is needed to develop the earthquake information applications from text to sound. The source of earthquake information is taken from an XML file that has been provided by BMKG. The application development uses the Waterfall method. The testing uses a blackbox with the boundary value analysis. The results of this study is text to speech application for earthquake information. Application testing using blackbox with the boundary value analysis for six different scenarios were successfully 100% running well without any errors